Motivasi Orang Tua Menyekolahkan Anaknya Ke Sekolah Keagamaan - Rahmi, Rahmi; Wirdati, Wirdati; Wardefi, Riza (Prodi Pendidikan Keagamaan Islam, 2023)
This study aims to identify the motivation of parents in Tampunik Village to send their children to religious schools. The type of research used is a qualitative research approach with a descriptive orientation. Based on the results of data processing and data analysis, the researcher draws the conclusion that the motivation of parents to send their children to religious schools is that children can learn religious knowledge in accordance with Islamic law and can practice it in their daily lives.